Performance analysis and load matching of a photovoltaic–thermoelectric hybrid system. (15th November 2015) - Lin, Jian; Liao, Tianjun; Lin, Bihong
Highlights: An update model of the PV–TEG hybrid system is proposed. Influences of irreversible losses and load resistances are considered. The maximum power output of the hybrid system is calculated. Effects of structure parameters and solar irradiance are analyzed. The loads of the hybrid system are optimally matched. Abstract: A photovoltaic–thermoelectric hybrid system consisting of photovoltaic (PV) modules and multi-couple thermoelectric elements is investigated by using a thermodynamic method. General formulas of the efficiency and power output of the hybrid system are derived. Optimum performance characteristics are revealed. The effects of structural parameters of the thermoelectric generator (TEG) and the operating conditions of PV modules on the performance of the hybrid system are analyzed. Optimal problems related to the load matching in the design of practical hybrid power generation systems are discussed. The results obtained here may offer some theoretical bases for the optimal design of real photovoltaic–thermoelectric hybrid power generation systems.